EFFECT OF FILE EDITING FREQUENCY ON SOFTWARE QUALITY - YATSENKO, ROMAN; SERDIUK, PAVLO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Understanding the impact of file editing frequency on software quality is crucial for maintaining and improving software reliability and maintainability. Software quality is a multifaceted concept that involves various aspects such as code maintainability, reliability, and adherence to principles like the Single Responsibility Principle (SRP). The Single Responsibility Principle emphasizes that a class or module should have only one reason to change, suggesting that high-quality software should be modular and focused. Frequent edits to files in a GIT repository can be indicative of underlying issues such as evolving requirements, poor initial design, or violations of SRP, leading to an increase in technical debt. This debt can manifest in the form of code that is difficult to maintain, prone to bugs, and challenging to extend. While existing research has explored the relationship between file editing frequency and software quality, this area remains under-explored, particularly in the context of the cumulative effect of these edits on long-term software quality. The objective of this study is to establish a more definitive link between the frequency of file edits and software quality. This will be achieved by introducing a new metric, the Consecutive File Edit Coefficient (CFE), and using it alongside traditional software quality metrics to analyze and compare the impact of frequent file edits. By doing so, this research aims to provide insights that can inform better practices in software development and maintenance. The comparative analysis across these open-source repositories reveals consistent patterns that highlight the risks associated with frequent file edits. High CFE values are often accompanied by increased complexity, more code smells, higher violations, and a greater number of bugs.